RECENT ADVANCES IN THE UNDERSTANDING AND MANAGEMENT OF ANCA-ASSOCIATED VASCULITIDES - Patryk Heryć; Karolina Kananowicz; Zuzanna Kudlińska; Honorata Juniewicz; Ryszard Łagowski; Julia Kosęda; Anna Jędrasiak; Zofia Laska; Marianna Latour; Jakub Piotrowski (International Journal of Innovative Technologies in Social Science, 2025)
Background. Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides (AAV) constitute a group of systemic vasculitides, comprising granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA). They primarily affect small vessels, resulting in a broad spectrum of clinical manifestations involving multiple organ systems, particularly those critical for sustaining vital functions. In recent years, substantial advances have been made in our understanding of these conditions. Aim. The objective of this study was to collect, analyze and synthesize the most recent evidence regarding ANCA-associated vasculitides. Material and methods. A comprehensive literature search of the PubMed database was conducted focusing on ANCA-associated vasculitides. The analysis encompassed the most recent and relevant case–control studies, observational studies, meta-analyses, as well as the latest recommendations of rheumatology societies concerning the etiopathogenesis, clinical presentation, diagnosis and management of AAV. Results and conclusion. ANCA-associated vasculitides are defined by the presence of specific autoantibodies directed against neutrophil antigens: proteinase 3 (PR3-ANCA) and myeloperoxidase (MPO-ANCA). These autoantibodies activate neutrophils and the complement system, leading to vascular wall injury. The upper respiratory tract and kidneys are the most commonly affected sites. Current therapeutic strategies are based on glucocorticoids in combination with immunosuppressive agents, with an increasing role for biologics such as rituximab and mepolizumab, enabling reduction of glucocorticoid exposure. Advances in the understanding of disease pathogenesis have facilitated the development of novel agents, including avacopan. Ongoing research efforts are directed toward the identification of new diagnostic biomarkers and therapeutic targets, as well as improving long-term outcomes and minimizing organ damage.